1984
DOI: 10.1002/ar.1092080415
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the density of microtubules in the central and peripheral axonal branches of the pseudounipolar neurons of lizard spinal ganglia

Abstract: The number and density of microtubules were determined in cross sections of the two branches (central and peripheral) of the bifurcating axon of the pseudounipolar neurons of the lizard thoracic spinal ganglia. In both the central and peripheral branches the average number of microtubules rose, while the microtubular density decreased with an increase in the cross-sectional area of the axonal branch: More precisely, a linear relationship was observed between the logarithm of the microtubular density and the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…That is, the number of MT does not change in terms of unit of axonal area in small or large axons. It has been previously reported that MT number depends on axonal area (Ochs et al, 1978;Pannese et al, 1984). However, for small axons, those results are consistent with the results reported here.…”
Section: Discussionsupporting
confidence: 94%
“…That is, the number of MT does not change in terms of unit of axonal area in small or large axons. It has been previously reported that MT number depends on axonal area (Ochs et al, 1978;Pannese et al, 1984). However, for small axons, those results are consistent with the results reported here.…”
Section: Discussionsupporting
confidence: 94%
“…In peripheral nerves, in the restricted range where the size of myelinated and nonmedullated axons overlaps, the microtubular content is also the same in both axonal classes (Pannese et al, 1984a;Facndez and Alvarez, 1986). On the other hand, in sensory neurons, radicular and peripheral branches of equal size and class exhibit different microtubular packings, as observed here in the rat and reported for cats and lizards (Fadic et al, 1985;Pannese et al, 1984b;Serra and Alvarez, 1989). All these observations indicate that the low microtubular content of radicular fibres is related to their lying in the root, and unrelated to being sensory or motor, myelinated or nonmedullated.…”
supporting
confidence: 77%
“…This we will call the radicular pattern. This asymmetry about the primary bifurcation of the sensory axon has been observed in toads, lizards and cats (FadiC et al, 1985;Pannese et al, 1984b;Saitua and Alvarez, 1989;Serra and Alvarez, 1989). Since axons of peripheral nerves share a common pattern of microtubular packing, FadiC et al (1985) conjectured that the radicular pattern may be shared with central nervous system (CNS) axons.…”
Section: Introductionmentioning
confidence: 81%
“…The second half of the 20th century saw an explosion of publications on lizards and snakes in The Anatomical Record . Topics include effects of controlled temperature and day length on gonadal development (Bartholomew, ), gross and microscopic anatomy of the liver and gall bladder (Ells, ), osteology and musculature (Evans, ; Bellairs and Bryant, ; Throckmorton, ; Throckmorton and Saubert, ; Rubolini et al, ; Hall, ; Payne et al, ; Direnzo and Stynoski, ), endocrine and reproductive biology (Miller, ; Fox, ; Cavazos and Feagans, ; Neaves, ; Jacobs and Sis, ; Rhoten and Hall, ; Rhoten, ; Jones et al, ; Jones and Summers, ; Moscona, ; Young et al, ), and neurobiology (Zika and Singer, ; Colborn and Adamo, ; Proske, ; Gundy and Wurst, ; Baird and Lowman, ; Sligar and Voneida, ; Yeager et al, ; Pannese et al, ; McDevitt et al, ; Amemiya et al, ). Among the endocrinology papers are three reports by long‐time American Association of Anatomists' member William B. Rhoten, whose research focused on the pancreas of the garter snake (Rhoten and Hall, ; Rhoten, ).…”
mentioning
confidence: 99%